PENERAPAN PEMBELAJARAN JARAK JAUH DI MASA PANDEMI PADA MATERI s DAN KSP KELAS XI IPA-1 SMAN 3 METRO - KARTIKA MARTI (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2023)
This Classroom Action Research was motivated by the covid-19 pandemic which demanded changes to the learning process from face-to-face to non-face-to-face. This makes the teacher as a facilitator in the learning process must think hard and smart to seek actions that answer the challenges of how the learning process in an emergency situation that does not allow face-to-face learning to occur, can still achieve the learning objectives as expected. On that basis the purpose of this PTK is to find out whether the application of distance learning methods, especially chemistry subject in the topic of s matter and Ksp in class of XI IPA-1 SMAN 3 Metro TP 2019/2020 via online (WhatsApp application and video conference application with PPT media) still makes students interest and have good results in learning, with descriptive percentage data analysis techniques. Data were taken from questionnaire data and test results. From the results of the data analysis, (1) the percentage of students who have achieved the KKM at each meeting averages above 75%, to be more precise, the average of the two cycles is 82%. (2) The percentage of students who still have a good interest even though the learning is distance learning reaches above 70%, that is, the average percentage of the two cycles is 83.82%. So it can be concluded that the application of distance learning methods, especially chemistry subject in the topic of s matter and Ksp in class of XI IPA-1 SMAN 3 Metro TP 2019/2020 via online (WhatsApp application, video conference with PPT media) still makes students have interest and learning outcomes the good one. ABSTRAKPenelitian Tindakan Kelas ini dilatarbelakangi oleh adanya pandemi covid-19 yang menuntut untuk melakukan perubahan proses pembelajaran dari tatap muka menjadi tidak tatap muka. Hal tersebut membuat guru sebagai fasilitator dalam proses pembelajaran harus berpikir keras dan cerdas untuk mengupayakan tindakan yang menjawab tantangan bagaimana proses pembelajaran dalam situasi darurat yang tidak memungkinkan pembelajaran tatap muka terjadi, tetap dapat mencapai tujuan pembelajaran seperti yang diharapkan. Atas dasar itu tujuan dari PTK ini adalah Mengetahui apakah penerapan metode pembelajaran jarak jauh (PJJ) khususnya mata pelajaran kimia materi s dan Ksp kelas XI IPA-1 SMAN 3 Metro TP 2019/2020 melalui daring (aplikasi WhatsApp dan aplikasi video converence dengan media PPT) tetap menjadikan peserta didik memiliki minat dan hasil belajar yang baik, dengan teknik analisis datanya deskriptip prosentase. Data diambil dari data kuesioner maupun hasil test. Dari hasil analisis data didapat,(1) Prosentase jumlah peserta didik yang telah mencapai KKM pada tiap pertemuannya rata-rata diatas 75%, lebih tepatnya mencapai rata-rata dari kedua siklus adalah 82%. (2)Prosentase jumlah peserta didik yang masih memiliki minat yang baik meski pembelajarannya adalah pembelajaran jarak jauh mencapai diatas 70%, yakni rerata prosentasi dari dua siklus adalah 83,82%. Sehingga dapat disimpulkan bahwa penerapan metode pembelajaran jarak jauh khususnya mata pelajaran kimia materi s dan Ksp kelas XI IPA-1 SMAN 3 Metro TP 2019/2020 melalui daring (aplikasi WhatsApp, video converence dengan media PPT) tetap menjadikan peserta didik memiliki minat dan hasil belajar yang baik.